Implementation of Policy for Prevention and Eradication of Abuse and Illegal Circulation of Drugs and Precursors (P4GN) at The National Narcotics Agency of Tangerang City Rehabilitation Section - Dina Nur Lestari; Oman Supriadi; Hasuri Waseh (International Journal of Social Sciences Review, 2022)
Drug Abuse and Illicit Trafficking in Drugs is one of the most pressing and complex problems, so it requires a comprehensive treatment. Many cases show how drugs have caused great losses, both in terms of material and non-material. The Prevention and Eradication of Illicit Narcotics Circulation and Abuse (P4GN) is a policy and strategy of the Indonesian government's to emphasize and protect the public from drug abuse and illicit trafficking. The National Narcotics Agency of Tangerang City is responsible for one of the tasks in the field of drug rehabilitation by increasing the capacity of medical and social rehabilitation institutions, both organized by the government and the community. Drug rehabilitation is the psychotherapeutic treatment given to drug addicts. It helps the patient to get rid of substance abuse as well as process abuse. This research uses descriptive qualitative research. To obtain data in accordance with the research focus, the research conducted interviews, observations and documentation. The results of this research showed the implementation has not been running optimally, there are several indicators that become obstacles in implementation, including limited resources, lack of communication between organizations that have not been intensely established, and have not fully matched the standards and objectives of the policy, and not fully involved formal or informal organizations. The supporting factors include the implementation of narcotics rehabilitation in accordance with the SOP, a positive response from the implementing agency, and the external environment (Economic, Social, Political) receiving a positive influence.